2013
DOI: 10.1080/09670262.2013.809610
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and digalactosyldiacylglycerol composition of dinoflagellates. VI. Biochemical and genomic comparison of galactolipid biosynthesis betweenChromera velia(Chromerida), a photosynthetic alveolate with red algal plastid ancestry, and the dinoflagellate,Lingulodinium polyedrum

Abstract: Chromera velia is a recently discovered, photosynthetic, free-living alveolate that is the closest free-living relative to nonphotosynthetic apicomplexan parasites. Most plastids, regardless of their origin, have membranes composed chiefly of two galactolipids, mono-and digalactosyldiacylglycerol (MGDG and DGDG, respectively). Because of the hypothesized shared red algal origin between the plastids of C. velia and dinoflagellates, our primary objectives were to examine how growth temperature affects MGDG and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 34 publications
(64 reference statements)
2
22
1
Order By: Relevance
“…Monounsaturated FA with 18 carbons were recorded in both chromerids in two forms: C18:1 n‐7 and C18:1 n‐9. Contrary to Dahmen's group presenting an identification of galactolipids with non‐polyunsaturated FAs C18 in C. velia , FID methodology was able to found one type of FA C18:2 n‐6 and two types of FA C18:3 n‐6 and C18:3 n‐3. All these FAs are present in different groups of marine photosynthetic organisms .…”
Section: Resultscontrasting
confidence: 89%
“…Monounsaturated FA with 18 carbons were recorded in both chromerids in two forms: C18:1 n‐7 and C18:1 n‐9. Contrary to Dahmen's group presenting an identification of galactolipids with non‐polyunsaturated FAs C18 in C. velia , FID methodology was able to found one type of FA C18:2 n‐6 and two types of FA C18:3 n‐6 and C18:3 n‐3. All these FAs are present in different groups of marine photosynthetic organisms .…”
Section: Resultscontrasting
confidence: 89%
“…We have found that like S. microadriaticum and species of Pyrocystis , C. velia also follows the pattern of modulating the sn ‐2 fatty acid of MGDG and DGDG, but rather than modulating a C 18 fatty acid it instead modulates 20:5 at 20°C to eicosatetraenoic (20:4) at 30°C (Dahmen et al . ). Thus, as we learn more about how dinoflagellates and their photosynthetic relatives respond to growth temperature with regard to their forms of MGDG and DGDG, we are finding that there are common adaptation mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of 16:0‐containing forms at 30°C does, however, agree with observations by Dahmen et al . () in the photosynthetic chromerid, Chromera velia Moore et al ., which produced 20:5/16:0 and 20:4/16:0 at 30°C but not 20°C. Similar results were observed by Adlerstein et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Dahmen et al . ), it was found that the predominantly C 18 sn ‐2 fatty acids of MGDG and DGDG were modified to be less saturated at 30°C, whereas the predominantly C 20 sn ‐1 fatty acid had the same degrees of unsaturation at both temperatures. In H. ostrearia and P. tricornutum (Dodson et al .…”
Section: Introductionmentioning
confidence: 95%